Investigation of Stress-Induced Cortisol Effects on Decision Making After Pharmacological Mineralocorticoid or Glucocorticoid Receptor Blockade - Deuter, Christian E; Weiß, Theresa-Svea; Kuehl, Linn K.; Otte, Christian; Wingenfeld, Katja (Pharmacopsychiatry, 2025)
Acute stress, potentially mediated by the stress-induced release of cortisol, affects decision-making processes. In the brain, cortisol activates two different types of receptors: the glucocorticoid receptor (GR) and the mineralocorticoid receptor (MR), each with different functional profiles. While previous studies suggest specific effects for MR and GR, the role of both receptor types in decision-making is insufficiently investigated.In this study, stress-induced effects of cortisol on decision-making processes were investigated after pharmacological receptor blockade of the MR (spironolactone, 300 mg) or the GR (mifepristone, 600 mg) in 318 healthy men (M=25.42, SD=5.01). After single-dose administration, participants were subjected to a social-evaluative stress task (Trier Social Stress Test, TSST), which reliably activates the HPA-axis, or a non-stressful control task (pTSST). Participants were randomly assigned to one study group: pTSST-placebo, TSST-placebo, TSST-spironolactone, or TSST-mifepristone. Subsequently, participants completed the Iowa Gambling Task (IGT) as an outcome measure. A mediation analysis was conducted to investigate direct effects of experimental manipulation in this study and indirect effects mediated by cortisol levels. The evidence for stress effects on decisions under ambiguity was positive.While stressed participants exhibited higher risk-taking, this was not the case in the TSST-spironolactone group, although this group had the most pronounced cortisol stress response. Thus, cortisol did not mediate this effect.The stress effect on decision-making was attenuated when MR was blocked. This corresponds to previous findings of increased risk-taking after MR activation and highlights a functional differentiation of both receptors for this domain.
Keywords: social stress; cortisol; mineralocorticoid receptor; Glucocorticoid receptor; decision making